Strange bodies : hybrid, text, and the human form : prints from the Sheldon Museum of Art : an exhibition, Focus Gallery, Sheldon Museum of Art Lincoln, Nebraska November 30-December 31, 2016 - Stewart, Alison G.; Stewart, Alison G. (Zea Books, 2016)
Catalogue for the Sheldon Museum of Art's exhibition "Strange Bodies: Hybrid, Text, and the Human Form," selected and curated by Professor Alison Stewart's "History of Prints: New Media of the Renaissance" class during the fall semester of 2016 in the School of Art, Art History, & Design at the University of Nebraska-Lincoln. Each of the eleven prints offers a different understanding or take on the body. Some are grounded in the physical and social aspects of humanity, while others present the body as a site for fantastic imagination and performance. Still others reference the printed page as a "body." Whether fish, fowl, or human, the body as seen in these prints continues to intrigue us across the centuries and show that even though times change, people and their concerns do not. 00Exhibition: Focus Gallery, Sheldon Museum of Art, Lincoln, USA (30.11.-31.12.2016)